Penerapan IoT (Internet Of Things) Untuk Pencegahan Dini Terhadap Kejahatan Begal - Tiara Ramayani; Bobby Kurniawan; Fauziah Wulandari; Fazrol Rozi; Cipto Prabowo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The purpose of this research is to develop a crime prevention system. The system is built with the concept of Internet of Thing using microcontroller technology. The system is designed to be able to transmit location data and heart rate of criminals in real time. 10 locations were selected to test the accuracy of location data and 6 student samples were selected to test heart rate data. The results of the study found that the system built can send location data accurately with an average distance (0.54 + - 0.75) meters, t (9) = -1.223, p =.234. Whereas for heart rate data there was no difference between the data from the system compared to the actual data (t (5) = -2.123, p =.223). For improvements to the system, it is necessary to add several variables such as body temperature and vibration.